Traditional taxonomy underestimates the number of species of Bokermannohyla (Amphibia: Anura: Hylidae) diverging in the mountains of southeastern Brazil since the Miocene. Issue 1 (31st December 2023) - Brunes, Tuliana O.; Pinto, Felipe C. S.; Taucce, Pedro P. G.; Santos, Marcus Thadeu T.; Nascimento, Luciana B.; Carvalho, Daniel C.; Oliveira, Guilherme; Vasconcelos, Santelmo; Leite, Felipe S. F.
Abstract : Despite the huge difference in land coverage between mountains and lowlands, most species are indeed found in mountains and foothills. The causes of this pattern have challenged biogeographers and evolutionary biologists. The Espinhaço and Mantiqueira Ranges are large mountain ranges from eastern Brazil that are global biodiversity hotspots located between the Brazilian Atlantic Forest (AF) and the Cerrado. However, Espinhaço and Mantiqueira species diversity may still be underestimated, either due taxonomic complexity or morphological cryptic species complexes. Two hylid frogs, Bokermannohyla nanuzae and Bokermannohyla feioi, are endemic, respectively, distributed in these two mountain ranges. These species were recently synonymized based on traditional taxonomy. We used data from the mitochondrial DNA (mtDNA) gene 16S and two nuclear genes to undertake phylogenetic and network, distance-based, and multispecies coalescent analyses on B. nanuzae, B. feioi, and an extensive outgroup dataset. We tested the monophyly of B. nanuzae, as well as the presence of candidate new species. Based on 16S phylogenetic analysis, We recovered B. nanuzae as paraphyletic, with B. sagarana nested within it. We recovered two main groups, with the geographic distribution generally corresponding to the Cerrado and AF boundaries. Probably due to ancestral polymorphism, both nuclear haplotype genealogies failed to distinguish B. nanuzae from the former B. feioi and/or from B. sagarana . The time-calibrated mtDNA tree revealed that B. martinsi, B. sagarana, and B. nanuzae have diverged during the Late Miocene, subsequently splitting into the remaining species/lineages during the Plio-Pleistocene. Taken together, our distance-based barcode and nuclear Bayesian analyses identified the former B. feioi, referred to as the AF group, as a distinct evolutionary lineage from B. nanuzae (Cerrado group). We provide the first insights into how different evolutionary lineages speciated in the highlands of southeastern Brazil and revalidated B. feioi for the AF group.